Evaluation of Survival Outcomes With Trimodal Therapy as Primary Therapy for Non-organ-confined Bladder Cancer - Yadong Guo (Frontiers in Oncology, 2019)
Background: Currently, the diagnosis of non-organ-confined bladder cancer (NOCBCa) has a very poor prognosis. For patients with NOCBCa, treatments such as radical cystectomy (RC) and systemic chemotherapy have shown survival benefits. However, the relative survival benefits of trimodal therapy (TMT) are unclear.Methods: Patients diagnosed with NOCBCa (cT4bN0M0, cTxN1-3M0, or TxNxM1) were identified in the Surveillance, Epidemiology, and End Results (SEER) database (2004–2015). Patients were grouped based on their definitive treatment for bladder cancer (RC or TMT with maximal transurethral resection, chemotherapy, or radiotherapy). All-cause mortality (ACM) and bladder cancer-specific mortality (BCSM) were assessed by Cox proportional hazard regression and competitive risk models.Results: A total of 2,988 patients met the inclusion criteria and were treated with RC (83.5%) or TMT (16.5%). Patients who underwent TMT had higher 5-year ACM (91.3%) and BCSM (88.8%) results compared to patients who underwent RC (82.6 and 75.0%, respectively) (P < 0.001). Adjusted hazard rate (AHR) analysis showed that TMT was associated with higher ACM (AHR: 1.33, 95% CI: 1.15–1.54, P < 0.001) and higher BCSM (AHR: 1.32, 95% CI: 1.13–1.54, P = 0.001). Subgroup analysis revealed not statistically significant between RC and TMT among patients aged ≥80 years (P > 0.05).Conclusions: Compared with TMT, RC is associated with a significant reduction in ACM and BCSM. However, the risks and survival benefits of RC should be weighed, especially in older patients, and our results further suggest that there may be no difference in the prognosis of RC and TMT in patients ≥80 years of age. These results are preliminary and emphasize the need for randomized controlled trials to compare TMT and RC.